2006
DOI: 10.1080/09511920500501632
|View full text |Cite
|
Sign up to set email alerts
|

A responsive demand management framework for the minimization of waste in convenience food manufacture

Abstract: Convenience food manufacture generates considerable waste through poor planning of production. This problem is particularly acute for products that have a very short shelf life and will be disposed of as waste should their shelf life expire. Chilled ready-meals are convenience foods with relatively short shelf lives and volatile consumer demands; their manufacture is based on forecasted volumes and when demand has been over-predicted, considerable wastes are created. This is referred to as OverProduction Waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Among those studies that included only current state mapping, four reported an associated lead time (Darlington and Rahimifard, 2006;Lehtinen and Torkko, 2005;Taylor, 2006b;Vlachos, 2015), one cycle time (Simons et al, 2003) while four studies reported none (Ahmed et al, 2015;Francis et al, 2008;Kennedy et al, 2013;Melvin and Baglee, 2008).…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Among those studies that included only current state mapping, four reported an associated lead time (Darlington and Rahimifard, 2006;Lehtinen and Torkko, 2005;Taylor, 2006b;Vlachos, 2015), one cycle time (Simons et al, 2003) while four studies reported none (Ahmed et al, 2015;Francis et al, 2008;Kennedy et al, 2013;Melvin and Baglee, 2008).…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
“…Kaizen), a requirement for achieving objectives in lean manufacturing, a number of additional tools were utilized either alone or in combination in various agri-food entities. Just-In-Time (JIT) or pull strategy was the most applied alongside VSM in nine studies (Darlington and Rahimifard, 2006;Folinas et al, 2015;Hossain and Uddin, 2015;Jiménez et al, 2012;Shobha and Subramanya, 2012;Tanco et al, 2013;Taylor, 2005Taylor, , 2006bVlachos, 2015) at both levels of analysis. 5S (sort, set in order, shine, standardize and sustain) methodology was mainly used in six studies (Engelund et al, 2009;Glover et al, 2014;Hossain and Uddin, 2015;Jiménez et al, 2012;Kennedy et al, 2013;Sathiyabama and Dasan, 2013) at a single plant level only.…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
See 3 more Smart Citations